Factors associated with health preparedness (istithaah) status among Hajj pilgrims in Indonesia: a cross-sectional study - Sugeng, Sugeng; Setiyarini, Sri; Probosuseno, Probosuseno; Kertia, Nyoman (Universitas Airlangga, 2025)
Introduction: The Hajj pilgrimage presents unique health challenges due to the large gatherings, particularly affecting elderly participants with preexisting conditions. Health istithaah, referring to physical and mental readiness for Hajj participation, is crucial for ensuring the safety of pilgrims. This study aimed to identify the factors associated with health istithaah status among Indonesian Hajj pilgrims. Methods: This descriptive correlational study examined 1,305 pilgrims scheduled for the 2023 Hajj pilgrimage. The data collected included health istithaah status, age, gender, and medical diagnoses based on ICD-10. The analysis employed Chi-Square tests and multivariate logistic regression (p < 0.05). Results: Of the participants, 772 (59.2%) had unassisted health istithaah, while 533 (40.8%) required assistance. Diabetes mellitus showed the highest association with requiring assistance (PR = 4.938, 95% CI = 3.354–7.270, p = 0.001), followed by symptoms and signs not classified elsewhere (PR = 4.071, 95% CI: 3.091–5.362, p = 0.001) and essential hypertension (PR = 3.467, 95% CI = 2.565–4.685). Age and multiple diagnoses were significantly associated with health istithaah status (p = 0.001), while gender showed no significant association (p = 0.246). Conclusion: Age, multiple diagnoses, and chronic conditions, particularly diabetes, were key factors associated with requiring health istithaah assistance among Indonesian Hajj pilgrims. These findings emphasize the need for targeted health assessments and support for high-risk pilgrims.